Studi Kelayakan Ekonomi Teknik Pembangunan Embung - . Suryanto (Universitas Bandar Lampung, 2011)
The government program focuses to increase the prosperity level of the community in poor village. In general, the location of poor village lies on narrow plateu with geologist condition of non aquiferous rocks and deep regional ground water level. One of the alternatives to overcome the problem is to construct ponds to catch the waterthat can be used in dry season.. The viability of ponds project is valued by analyse the agro-economy. It is needed to weight beetwen cost componenst and benefit component; and compare the condition without project in present condition, future without project and future with project. The parameters that are used to value the engineering economics viability of the project are NPV, IRR, BCR and Pay Back Period. Employing the inflation rate of 12%, ROR 20% and economic life of 20 years, it is known that all ponds have the positive parameter values and viable to be constructed.